Innovations in tricuspid valve intervention. (March 2017) - El-Eshmawi, Ahmed; Tang, Gilbert H.L.; Verma, Subodh; Yanagawa, Bobby; Ruel, Marc; Adams, David H.
Abstract : Purpose of review: Tricuspid valve disease has received much less attention in terms of intervention. The main reason for this is the widely held belief that treatment of left-sided valve disease leads to resolution of functional tricuspid regurgitation. Recent data show that tricuspid regurgitation is not benign and that many patients will benefit from intervention at the time of left-sided valve surgery, or in isolated tricuspid disease. This review describes the latest surgical and interventional options and strategies. Recent findings: Latest valve guidelines now recommend a more aggressive surgical approach to the treatment of moderate or severe tricuspid regurgitation, with annuloplasty being the preferred technique. Guidelines now also promote treatment of isolated significant tricuspid dilatation even without significant regurgitation, as a prophylactic strategy to prevent disease progression. This renewed interest in surgical repair has been accompanied by development of newer tricuspid annuloplasty rings. For patients in whom surgery would be high risk, transcatheter therapies are emerging as a promising alternative. Various repair devices have reported early experience. Summary: Recent surgical and transcatheter innovations in the treatment of tricuspid valve disease are promising and have the potential of removing the stigma of the tricuspid valve as the 'forgotten valve'.